(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Cluster of Metabolic syndrome is closely associated with various types of cancer, fatty liver disease, cardiovascular diseases, neurological dysfunction and neural tube defects. Alpha feto-protein is still used as a biomarker for liver cancer and neonatal screening worldwide but relation between metabolic syndrome and the exact role of alpha fetoprotein in adult is unclear. The recent study evidenced that there is a relationship with alpha feto-protein and cluster of metabolic syndrome. The aim of the study to analyze the relationship between alpha feto-protein and various metabolic syndrome and alpha fetoprotein may be used as metabolic markers through the following linkages: (i) The linkage of alpha-fetoprotein with demographic parameter (ii) The linkage of alpha-fetoprotein with Diabetes, Hypertension, Dyslipidemia Obesities, nonalcoholic steatohepatitis (NASH) (iii) The linkage of alpha-fetoprotein with Cancer, (iv) The linkage of alpha-fetoprotein with liver disease. The alpha feto-protein elevation which might be useful for early diagnosis and prevalence of liver disease, cancer, cluster of metabolic syndrome and neonatal defects.